Variability analysis of Sukun durian plant (Durio zibethinus) based on RAPD marker - ISMI PUJI RUWAIDA; SUPRIYADI SUPRIYADI; PARJANTO PARJANTO (Smujo International, 2009)
Abstract. Ruwaida IP, Supriyadi, Parjanto. 2009. Variability analysis of Sukun durian plant (Durio zibethinus) based on RAPD marker. Nusantara Bioscience 1: 84-91. The purpose of the study is to assess the diversity of the durian varieties of Sukun, Sunan, Kani, Monthong, and Petruk; and Sukun durian variety is grown in different regions based on RAPD markers. Materials research is durian leaves of Sukun, Sunan, Kani, Monthong and Petruk from Ranukutri Garden Seeds, Karanganyar, and also Sukun durian leaf from Gempolan Karanganyar, Jepara and Salatiga. Then performed DNA analysis on samples of leaves that began the isolation of DNA, test of DNA quantity and quality, primer selection, and amplification with PCR. Visualization of PCR performed by electrophoresis using EtBr that generate DNA bands. DNA bands were then analyzed with NTSYS program to get durian diversity among varieties of durian and between Sukun durian at different planting areas. Six RAPD polymorphic primer was used, namely OPA-01, OPA-02, OPA-07, OPA-16, OPA-18, and OPA-19. Banding pattern of DNA amplification show the existence of diversity among varieties of Sukun durian, Sunan, Kani, Monthong and Petruk and show the diversity of Sukun durian grown in different areas. Dendrogram indicated that five durian varieties tend to segregate, whereas Sukun, Sunan, Monthong, and Petruk in one group, which split with Kani. Dendrogram also indicated that Sukun planted in different regions resulted in two groups, Sukun from Gempolan Karanganyar and Salatiga in one group, while the second group consisted of Sukun from Ranukutri seed garden Karanganyar and Jepara. generate DNA bands. DNA bands were then analyzed with NTSYS program to get durian diversity among varieties of durian and between Sukun durian at different planting areas. Six RAPD polymorphic primer was used, namely OPA-01, OPA-02, OPA-07, OPA16, OPA-18, and OPA-19. Banding pattern of DNA amplification show the existence of diversity among varieties of Sukun durian, Sunan, Kani, Monthong and Petruk and show the diversity of Sukun durian grown in different areas. Dendrogram indicated that five durian varieties tend to segregate, whereas Sukun, Sunan, Monthong and Petruk in one group, which split with Kani. Dendrogram also indicated that Sukun planted in different regions resulted in two groups, Sukun from Gempolan Karanganyar and Salatiga in one group, while the second group consisted of Sukun from Ranukutri seed garden Karanganyar and Jepara.